Teach yourself visually wireless networking - Tidrow, Rob.; Carter, Todd W. (Hoboken, NJ : Wiley Pub., 2006)
A guide to wireless computer networks cover such topics as installing hardware, configuring networks, creating computer-to-computer networks, administering wireless networks, and network security.
Chapter 1 Introducing Wireless Networking -- Chapter 2 Setting Up Wireless Network Hardware -- Chapter 3 Installing Wireless Hardware in PCs -- Chapter 4 Configuring Wireless Networks -- Chapter 5 Creating Computer-to-Computer Networks -- Chapter 6 Software for Wireless Computing -- Chapter 7 Communicating with Wireless Computers -- Chapter 8 Using Wireless Computers for Business Presentations -- Chapter 9 Using Wireless Computers for Entertainment -- Chapter 10 Working on Wireless Networks -- Chapter 11 Administering Wireless Networks -- Chapter 12 Securing Wireless Networks -- Chapter 13 Connecting on the Road -- Chapter 14 Improving Network Performance -- Chapter 15 Troubleshooting a Wireless Network.
Previous ed. by Todd W. Carter and Paul Whithead.
Includes index.
1
Keywords: Wireless communication systems; Computer networks